2018
DOI: 10.1002/cam4.1581
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic role and dynamic changes in cerebrospinal fluid neopterin during treatment of patients with primary central nervous system lymphoma

Abstract: This study aimed at evaluating the diagnostic and prognostic role of neopterin (Npt) concentration in the cerebrospinal fluid (CSF) of patients with primary central nervous system lymphoma (PCNSL). Ninety‐nine patients were enrolled in this retrospective study; these included patients with PCNSL (n = 21), other brain tumors (n = 44), and inflammatory diseases (n = 34). CSF Npt concentration was measured using ELISA. Receiver operating characteristic (ROC) curve analysis was performed to assess the discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Neopterin (Npt), interleukin (IL)-6 or IL-10 and microRNA are considered to play roles in the diagnosis of PCNSL, with relatively high sensitivity and specificity ( 9 12 ). However, in our retrospective study on CSF Npt, this biomarker showed a false-positive ratio of 16%, and the accuracy of clinical diagnosis was greatly reduced ( 13 ). IL-6 is a potent pluripotent inflammatory factor produced by cells that promotes the growth and differentiation of lymphocytes ( 14 ); it is a powerful growth and differentiation factor for lymphocytes that is secreted by various cells, such as benign and malignant B lymphocyte, monocytes, macrophages, fibroblasts and hepatocytes ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 86%
“…Neopterin (Npt), interleukin (IL)-6 or IL-10 and microRNA are considered to play roles in the diagnosis of PCNSL, with relatively high sensitivity and specificity ( 9 12 ). However, in our retrospective study on CSF Npt, this biomarker showed a false-positive ratio of 16%, and the accuracy of clinical diagnosis was greatly reduced ( 13 ). IL-6 is a potent pluripotent inflammatory factor produced by cells that promotes the growth and differentiation of lymphocytes ( 14 ); it is a powerful growth and differentiation factor for lymphocytes that is secreted by various cells, such as benign and malignant B lymphocyte, monocytes, macrophages, fibroblasts and hepatocytes ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 86%
“…The most common strategy involves correlating biomarkers with tumor volume, reasoning that higher tumor burden contributes to higher biomarker production. 27,66,[78][79][80][81][82] Following the same logic, biomarkers have also been correlated with treatment response, 80,[83][84][85][86][87][88][89][90][91][92][93][94][95] and decline after surgical resection. 44,46,[96][97][98][99][100] More direct methods of establishing neoplastic origins involve spatial localization of biomarkers using immunohistochemistry or in situ hybridization (Data Supplement, Table S3).…”
Section: Tumor Specificity and The Cell-of-origin Problemmentioning
confidence: 99%
“…Neopterin is a metabolite associated with T-helper cell-mediated immunity and is elevated in CSF of PCNSL, bacterial meningitis and viral meningoencephalitis, relative to other non-CNSL tumors (GBM, glioma, BrM), neuro-in ammatory, and healthy controls (Table S9). 92,140,141 Given its dysregulation in neuro-infection, neopterin levels must be interpreted within clinical context. The performance of neopterin in diagnosing PCNSL in the setting of space-occupying lesions is excellent, with sensitivities ranging between 95.2-96% and negative predictive values between 97.4-98% (Table 3).…”
Section: Brain Metastasismentioning
confidence: 99%
“…Beyond its diagnostic utility, neopterin correlates with changes in PCNSL tumor size on MRI. 92 In patients with space-occupying lesions, neopterin is highly sensitive biomarker with excellent NPV to rule out PCNSL. 140…”
Section: Brain Metastasismentioning
confidence: 99%